Catholicism a very short introduction - O'Collins, Gerald 1931- (Very short introductions, 2017)
Among the topics covered in this introduction to the largest and oldest institution in the world are the origins of the Catholic Church, how Catholicism has changed and adapted over the centuries and the challenges the Catholic Church faces in the 21st century